Placenta peptides: antibacterial effects - I. Yu. Torshin; T. E. Bogacheva; O. A. Gromova (LLC "Publisher OKI", 2024)
Mass spectrometric sequencing of peptides in Laennec indicated the presence of 5 peptides in the drug, the biological activity of which may determine the antibacterial properties of the drug. The most significant result of this study is the presence in Laennec of a fragment of the antibacterial peptide cathelicidin (LL-37), an important vitamin D-dependent factor of innate immunity. Other Laennec peptides help reduce excess inflammation by inhibiting the activity of the NF-kB protein, which mediates the effects of TNF-α.